2014
DOI: 10.1073/pnas.1405016111
|View full text |Cite
|
Sign up to set email alerts
|

DNA topology confers sequence specificity to nonspecific architectural proteins

Abstract: Topological constraints placed on short fragments of DNA change the disorder found in chain molecules randomly decorated by nonspecific, architectural proteins into tightly organized 3D structures. The bacterial heat-unstable (HU) protein builds up, counter to expectations, in greater quantities and at particular sites along simulated DNA minicircles and loops. Moreover, the placement of HU along loops with the "wild-type" spacing found in the Escherichia coli lactose (lac) and galactose (gal ) operons preclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…This phenomenon of cooperative kink formation due to bending in small DNA loops has also been seen experimentally with cryo-EM (31), although the sequence dependence of this phenomenon could not be determined. Simulation studies of the DNA loop stabilizing protein HU have demonstrated a cooperative uptake of proteins that introduce sharp kinks in DNA at antipodal sites along a closed DNA circle, highlighting the critical role played by DNA topology in inducing site-specific recognition by otherwise non-specific DNA binding proteins (43). …”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon of cooperative kink formation due to bending in small DNA loops has also been seen experimentally with cryo-EM (31), although the sequence dependence of this phenomenon could not be determined. Simulation studies of the DNA loop stabilizing protein HU have demonstrated a cooperative uptake of proteins that introduce sharp kinks in DNA at antipodal sites along a closed DNA circle, highlighting the critical role played by DNA topology in inducing site-specific recognition by otherwise non-specific DNA binding proteins (43). …”
Section: Resultsmentioning
confidence: 99%
“…28 Their numerical simulations revealed a number of interesting physical mechanisms, including HU-assisted loop formation 24,26 and DNA-directed sequence speci¯city of nonspeci¯c bending proteins. 25 However, all the above mentioned models did not reveal the mechanism underlying the HU cooperative clustering and the related topological patterns.…”
Section: Introductionmentioning
confidence: 95%
“…Olson and co-workers took the modeling of HU-DNA complexes beyond the traditional statistical mechanics approach by considering realistic three-dimensional (3D) structural and mechanical features. [19][20][21][22][23][24][25][26][27] The fact that their coarse-grained model was based on elastic forces made the realization of a great number of atoms possible. 28 Their numerical simulations revealed a number of interesting physical mechanisms, including HU-assisted loop formation 24,26 and DNA-directed sequence speci¯city of nonspeci¯c bending proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the GalR loop requires both negatively supercoiled DNA and HU (Lia et al 2003). Simulations of the binding of HU to the GalR and LacR loops indicate that DNA superhelicity can direct the binding of HU to a specific site within the loop and confer an optimal trajectory on the looped DNA for loop closure by the repressor protein (Wei et al 2014). By untwisting constrained DNA, HU has the potential to alter the average helical repeat in the loop and so enable optimal interactions.…”
Section: H-ns Nucleoprotein Complexesmentioning
confidence: 99%